Effect of Computer Simulation on Secondary School Students’ Interest in Algebra - Egara, Felix O.; Eseadi, Chiedu; Nzeadibe, Augustina C. (Education and information technologies, 2022)
This study examined the effect of using computer simulation on students’ interest in algebra. A quasi-experimental design was employed. A sample of fifty-four students (age range: 12-14years old) drawn from two schools constituted the subjects for the study. Two JSS 2 classes in each school were assigned through balloting to experimental and control groups. The subjects were taught by their regular mathematics teachers that served as an assistant in the research. Both groups (experimental and control) were pre-and post-tested. The Algebra Interest Inventory (AII) was the instrument utilized for data collection for the study and it has a reliability coefficient of 0.76. Data collected were subjected to analysis using SPSS software. The mean and standard deviation were used for reporting the research questions and analysis of covariance (ANCOVA) was for testing the hypotheses at .05 level of significance. Analysis of the results showed that the mean interest scores of students taught algebra with computer simulation was significantly higher than those taught with the conventional method. The result also showed that there was no significant difference between the mean interest scores of male and female students taught algebra with computer simulation. The study made some recommendations and one of them is that the use of computer simulation in mathematics lessons should be encouraged in the mathematics teaching and learning process especially as it arouses students’ interest.